Adoption of Innovation in Herpes Simplex Virus Keratitis. (November 2020) - Chodosh, James; Ung, Lawson
Abstract : Abstract: Herpes simplex keratitis, caused primarily by human herpes simplex virus type 1 (HSV-1), remains the most common infectious cause of unilateral blindness and vision impairment in the industrialized world. Major advances in the care of HSV keratitis have been driven in large part by the landmark Herpetic Eye Disease Study randomized clinical trials, which were among the first in ophthalmology to reflect emerging trial conventions, including multicenter subject enrollment, double-masking, placebo controls, and a priori sample size determinations. The results of these trials now form much of the evidence basis for the management of this disease. However, management patterns in clinical practice often deviate from evidence-based care. These perceived quality gaps have given rise to the evolving field of implementation science, which is concerned with the methods of promoting the application of evidence-based medicine within routine care. To overcome variations in the quality and consistency of care for HSV keratitis, a range of clinical- and technology-based innovations are proposed. The most pressing needs include the following: a rational and tractable disease classification scheme that provides an immediate link between the anatomical localization of disease (corneal epithelial, stromal, or endothelial) and the appropriate treatment, and the actualization of an electronic medical record system capable of providing evidence-based treatment algorithms at relevant points of care. The latter would also input data to population-wide disease registries to identify implementation-rich targets for quality improvement, education, and research. These innovations may allow us to reduce the human and economic burdens of this highly morbid, and often blinding, disease.